Recent Applications of Silver Amalgam Electrodes for Analysis of Pharmaceuticals and Vitamins - Smarzewska, Sylwia; Metelka, Radovan; Bas, Boguslaw; Vytřas, Karel (My University, 2018)
The features and applications of silver amalgam electrodes in electroanalysis of pharmaceuticals and vitamins are summarized in this review. The state-of-the-art in the preparation and construction of solid silver amalgam electrodes for prolonged and user-friendly use is presented. Although not as widely spread as other electrode materials, silver amalgam possesses a unique and viable combination of favorable electrochemical properties, which are close to ideal mercury electrodes, non-toxic character, high durability and mechanical stability, if properly prepared. Its capability of conducting the redox processes at highly negative potentials is essential for the analysis of large number of bioactive organic compounds. The review features also overview information for each application in drug or vitamin analysis divided to the sections according to the construction variants of silver amalgam electrodes.
Současné aplikace elektrod ze stříbrné amalgámy pro analýzu léčiv a vitaminů
Keywords: Silver amalgam electrodes; Drugs; Vitamins; Pharmaceuticals; Clinical analysis; Stříbrné amalgámové elektrody; Léky; Vitaminy; Léčiva; Klinická analýza